Automotive glass beading polyurethane material and method for producing the same
Patent Information
- Application Number
- CN202211381401.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-11-07
AI Technical Summary
解决现有的聚氨酯材料快脱模和制品高性能无法同时满足的技术问题
[0035]与现有技术相比,本发明具有以下优点及有益效果:本发明提供一种通过合成二元胺改性的二苯基甲烷二异氰酸酯与其它改性异氰酸酯搭配使用,配合A料组分调整,提高体系中的脲基含量,制成了一种高性能汽车玻璃包边用聚氨酯材料,脱模时间可降低至25s并且铁件未加热条件下制品的粘接性、强度、韧性和收缩性能优异。解决了现有汽车天窗玻璃包边材料为保证质量无法进一步提高生产效率的问题。
Smart Images

Figure BDA0003928465500000031 
Figure BDA0003928465500000041 
Figure BDA0003928465500000091
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyurethane materials, specifically relating to a high-performance automotive glass edging polyurethane material and its preparation method, and more particularly to a high-performance automotive glass edging polyurethane material containing a diamine-modified isocyanate component and its preparation method. Background Technology
[0002] According to the overall vehicle design, automotive glass needs to be processed into products with edging. Automotive glass edging can be divided into four types based on the material: polyurethane (PU), thermoplastic elastomer (TPE) (including SEBS and TPV), ethylene propylene diene monomer (EPDM), and polyvinyl chloride (PVC). Common processes include full-circumference edging with adhesive strips, PVC / PUR injection molding edging, PU-bonding edging, PU direct extrusion edging, and 3M tape bonding edging. Glass edging materials integrate appearance, function, and safety, serving the purposes of bonding, fixing, sealing, and decoration. Polyurethane injection molding (PU-RIM) is a process that uses liquid polyurethane raw materials, which are mixed under high pressure and directly injected into a mold for rapid polymerization and curing into polyurethane products. Compared with traditional edge-wrapping processes, it has many advantages: the liquid raw materials are injected at room temperature, resulting in lower energy consumption, lower injection pressure, and less stringent mold requirements; it is a one-piece molding process with short demolding time and high production efficiency; it offers high flexibility in product design, a wide range of adjustable formulations, and the polyurethane raw material has good fluidity, making it suitable for various large-sized and complex-shaped glass products, especially automotive sunroof glass; polyurethane products have good performance and strong adhesion to glass. Since the introduction of PU-RIM technology into the production of automotive glass edge-wrapping products abroad in the 1990s, it has gradually replaced traditional production processes.
[0003] Polyurethane materials used for automotive glass edging are broadly classified into aliphatic and aromatic categories. Aliphatic materials, primarily based on the IPDI system, offer excellent light aging performance but suffer from poor physical properties and high prices, leading to reliance on imports and a declining market share in China. Aromatic materials, mainly based on the MDI system, possess a benzene ring structure, resulting in products with better strength and toughness, and hold a dominant position in the domestic market. The bonding of RIM polyurethane elastomer to glass and metal components is a crucial step in manufacturing glass edging products, directly impacting product safety. With ongoing research, many researchers have attempted to optimize existing production processes, reducing demolding time, eliminating the glass primer coating process, and eliminating the preheating process for metal components while maintaining product quality and bonding strength. This aims to improve production efficiency and reduce costs, but currently, it is impossible to simultaneously improve both product quality and efficiency. Patent CN111732703A discloses a highly adhesive polyurethane material for automotive glass edging and its preparation method. This material exhibits excellent adhesion to unheated iron parts, meeting the requirements for sunroof glass edging products. This eliminates the need for preheating the iron parts, allowing direct use in production and improving efficiency. However, the patent requires 60 seconds of pressure holding and curing before demolding after the polyurethane concentrate is injected into the mold. Compared to the conventional 30-40 second demolding process, this reduces production efficiency to some extent. Furthermore, the shortened pressure holding time in the conventional 30-40 second demolding process reduces the bonding effect, failing to fundamentally solve the problem. Therefore, structural improvements are needed from the material's perspective to find a better solution.
[0004] Patent CN114591480A discloses a method for preparing a polyurea-based polymer. This method obtains a pure polyurea-based polymer with both soft and hard segments through the polymerization reaction of a diamine and a diisocyanate. The strong polarity of the urea group and the stable conjugation effect of the diamide structure improve the low-temperature adhesion and toughness of the polyurea-based adhesive. Patent CN109321123A also prepared a similar pure polyurea-based polymer for use in the preparation of a one-component anti-sagging polyurethane waterproof coating. In the preparation of the above-mentioned polyurea-based polymers, the molar ratio of diamine to isocyanate is close to 1:1, resulting in a very vigorous reaction. Solution polymerization is commonly used, but the post-processing is complex, and the resulting polymer is pure polyurea. If bulk polymerization is used, it will cause explosive agglomeration, terminating the reaction.
[0005] Currently, the RIM polyurethane elastomers used for glass edging are mainly polyurethane / urea systems. The introduction of urea groups increases the polarity of the hard segments, reduces the thermodynamic compatibility between the hard and soft segments, strengthens the microphase separation between the hard and soft segments, and simultaneously improves its cohesive strength and surface energy, thereby enhancing its physical properties and adhesive strength. The urea group structure in the polyurethane / urea system is generally synthesized from amine chain extenders in component A. Its reaction rate is extremely fast. While providing urea groups, it also significantly increases the viscosity of the polyurethane in the early stage of the reaction, causing a decrease in flowability and affecting the molding of the product. If it is necessary to maintain the flowability in the early stage of the reaction, the amount of catalyst needs to be reduced. However, reducing the amount of catalyst will cause the reaction rate of the entire system to be extremely uneven, resulting in poor curing of the product in the later stage. These two factors are contradictory. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a polyurethane material for automotive glass edging and its preparation method. Starting with component B, it uses a low-activity diamine prepolymer modified isocyanate and introduces a urea group structure, which ensures that the flowability in the early stage of the reaction is not affected, while also ensuring good post-curing, stable and reliable reaction, and excellent product performance. This solves the technical problem that existing polyurethane materials cannot simultaneously achieve fast demolding and high-performance products.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A polyurethane material for automotive glass edging, comprising the following components in parts by weight:
[0009] Material A includes:
[0010]
[0011]
[0012] Material B contains diamine-modified diphenylmethane diisocyanate and modified isocyanate.
[0013] The preparation method of diamine-modified diphenylmethane diisocyanate according to the present invention includes the following steps: reaction of diphenylmethane diisocyanate and diamine.
[0014] In the preparation method of diamine-modified diphenylmethane diisocyanate according to the present invention, the molar ratio of the active hydrogen atoms of the diamine to the isocyanate groups in the diphenylmethane diisocyanate is (0.001-0.2):1.
[0015] As a preferred embodiment, the preparation method of the diamine-modified diphenylmethane diisocyanate of the present invention includes the following steps: adding a diamine to the diphenylmethane diisocyanate at 40-65°C, and after the diamine is added, reacting at 70°C-90°C for 1.5-3 hours.
[0016] As a preferred embodiment, the preparation method of the diamine-modified diphenylmethane diisocyanate of the present invention is carried out in the presence of a polymerization inhibitor.
[0017] The polymerization inhibitors described in this invention include, but are not limited to, one or more of benzoyl chloride, adipic acid chloride, phosphoric acid, dimethyl sulfate, resorcinol, and hydroquinone.
[0018] The diamine described in this invention is C2-C 32 Diamine compounds; preferably, the diamine includes one or more of octanediamine, decanediamine, dodecanediamine, isophoronediamine, diaminodicyclohexylmethane, dimethyldiaminodicyclohexylmethane, and polytetramethylene glycol bis(p-aminobenzoate). More preferably, polytetramethylene glycol bis(p-aminobenzoate) has lower reactivity, a stable and controllable reaction process, and the terminal amino group reacts to form urea groups, increasing polarity while its long molecular chain structure further improves the toughness of the product.
[0019] In the B material of this invention, the modified isocyanate is selected from one or more of carbodiimide-modified isocyanate, urethane-modified diisocyanate, and polyisocyanate. Preferably, the carbodiimide-modified isocyanate is carbodiimide-modified MDI, which is produced by heating MDI to 200°C in the presence of phosphides to generate an MDI modified product containing a carbodiimide structure, such as WANNATE 1631 from Wanhua Chemical; the urethane-modified diisocyanate is generally produced by reacting MDI with polyether polyols or polyester polyols to generate urethane-modified MDI with -NCO terminal groups, such as WANNATE 8617B from Wanhua Chemical; the polyisocyanate is polyMDI, which is a mixture containing polymethylene polyphenyl diisocyanates with different functionalities, such as WANNATE PM200 from Wanhua Chemical.
[0020] The content of diamine-modified diphenylmethane diisocyanate in component B is 30-60%, based on the total weight of component B.
[0021] The isocyanate group (NCO) mass fraction of material B in this invention is 16-30%, preferably 23-28%.
[0022] The preparation method of material B of the present invention includes the following steps: mixing the diamine-modified diphenylmethane diisocyanate and the modified isocyanate, and stirring for 15-30 minutes.
[0023] The polyether polyol of the present invention has a functionality of 3, a hydroxyl value of 10-80 mgKOH / g, and polymer units of propylene oxide and ethylene oxide, wherein the ethylene oxide accounts for 5%-50%.
[0024] The polyether polyol of the present invention has a functionality of 2, a hydroxyl value of 10-120 mgKOH / g, and a polymerization unit of propylene oxide, or propylene oxide and ethylene oxide, wherein the ethylene oxide accounts for 5%-50%.
[0025] The alcohol chain extender described in this invention is one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,2-pentanediol, hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, diethylene glycol, neopentanediol, glycerol, or trimethylolpropane.
[0026] The amine chain extender described in this invention is one or more of the following: diethyltoluenediamine, dimethylthiotoluenediamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 2,4-diamino-3-methylthio-5-propyltoluene, N,N-dimethyl-1,3-propanediamine, toluenediamine, ethylenediamine, butanediamine, and hexamethylenediamine.
[0027] The catalysts described in this invention include organometallic catalysts and amine catalysts, with a mass ratio of 1:1-5.
[0028] Preferably, the organometallic catalyst comprises one or more of the following: dibutyltin dilaurate, dioctyltin dilaurate, stannous octoate, dibutyltin diacetate, dibutyltin thiolate, dioctyltin thiolate, dioctyltin dithioacetate, dimethyltin dithioacetate, zinc carboxylate, and bismuth carboxylate.
[0029] Preferably, the amine catalyst comprises a tertiary amine catalyst, more preferably at least one of triethylenediamine, dimethylaminopropylamine diisopropanol, tetramethyldipropylenetriamine, and bis(dimethylamino)-2-propanol;
[0030] The anti-aging additives include one or more of light stabilizers, ultraviolet absorbers, and antioxidants.
[0031] Preferably, the light stabilizer comprises a hindered amine free radical scavenger, suitable examples including but not limited to one or more of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0032] Preferably, the ultraviolet absorber comprises one or more of benzotriazole, benzophenone, and triazine ultraviolet absorbers, suitable examples including but not limited to 3-[3-(2-H-benzotriazole-2-yl)-4-hydroxy-5-tert-butylphenyl]-propionic acid-polyethylene glycol ester, 2-(2H)-benzotriazole-2-yl)-6-dodecyl-4-methylphenol, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazole-2-yl)-4,6-di-tert-pentylphenol, N-(ethoxycarbonylphenyl)-N'-ethyl-N'-phenylformamidinium, 2,(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole, and 2-hydroxy-4-n-octyloxybenzophenone.
[0033] Preferably, the antioxidant includes, but is not limited to, one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate isooctyl ester, 2,6-di-tert-butyl-4-methylphenol, and 3,5-di-tert-butyl-4-hydroxyphenylpropionate isotriadecyl ester.
[0034] A method for preparing an automotive glass edging product includes the following steps: Using a reaction injection molding process, materials A and B are mixed uniformly in a mass ratio of A:B = 100:40-75, preferably 100:50-65, using a high-pressure foaming machine. The mixture is then poured into a mold containing an iron part and surface-activated glass. After curing for 25-35 seconds, the mold is opened to obtain the automotive glass edging product. The material temperature is maintained at 30-45℃, and the mold temperature is maintained at 80℃-120℃.
[0035] Compared with existing technologies, this invention has the following advantages and beneficial effects: This invention provides a high-performance polyurethane material for automotive glass edging, produced by combining diphenylmethane diisocyanate modified with diamine and other modified isocyanates, and adjusting the urea content in the system by adjusting the A component. The demolding time can be reduced to 25 seconds, and the product exhibits excellent adhesion, strength, toughness, and shrinkage properties even without heating the iron parts. This solves the problem that existing automotive sunroof glass edging materials cannot further improve production efficiency to ensure quality. Detailed Implementation
[0036] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto.
[0037] Unless otherwise specified in the embodiments and comparative examples of this invention, the conditions were performed under conventional conditions or conditions recommended by the manufacturer. All raw materials and reagents used, unless otherwise specified, were commercially available products.
[0038] The raw materials used in the examples and comparative examples are shown below:
[0039] Material A components:
[0040] Polyether polyol 1, functionality 3, glycerol-initiated, hydroxyl value 35 mg KOH / g, polymerized from propylene oxide and ethylene oxide, ethylene oxide content 10%, based on the total mass of propylene oxide and ethylene oxide;
[0041] Polyether polyol 2, functionality 3, glycerol-initiated, hydroxyl value 28 mg KOH / g, polymerized from propylene oxide and ethylene oxide, ethylene oxide content 15%, based on the total mass of propylene oxide and ethylene oxide;
[0042] Polyether polyol 3, functionality 2, propylene glycol starting material, hydroxyl value 28 mg KOH / g, polymerized from propylene oxide and ethylene oxide, ethylene oxide content 15%, based on the total mass of propylene oxide and ethylene oxide;
[0043] Polyether polyol 4, functionality 2, propylene glycol starting material, hydroxyl value 28mgKOH / g, propylene oxide polymerization;
[0044] Alcohol chain extenders: ethylene glycol;
[0045] Amine chain extender: diethyltoluenediamine;
[0046] Catalysts: Triethylenediamine, Dioctyltin Thiol;
[0047] Anti-aging additives: 2-(2H)-benzotriazol-2-yl)-6-dodecyl-4-methylphenol, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol ester;
[0048] Pigment: Black pigment;
[0049] Component B:
[0050] Diamines: polytetramethylene glycol bis(p-aminobenzoate), dodecanediamine, isophoronediamine, dimethyldiaminodicyclohexylmethane;
[0051] Polymerization inhibitor: adipyl chloride;
[0052] WANNATE MDI-100F, NCO content 33.6wt%, Wanhua Chemical;
[0053] Carbodiimide-modified isocyanate: WANNATE 1631, NCO content 29.0wt%, Wanhua Chemical;
[0054] Carbamate-modified isocyanate: WANNATE 8617B, NCO content 22.5wt%, Wanhua Chemical.
[0055] Polyurethane materials for automotive glass edging were prepared according to the components shown in Table 1 in Examples 1-4 and Comparative Examples 1-4.
[0056] Table 1 Raw Materials and Usage
[0057]
[0058] Example 1
[0059] Preparation of component A: The measured materials shown in Table 1 are added into the reactor and stirred at room temperature for 2 hours, and then discharged to obtain component A;
[0060] Preparation of Material B:
[0061] According to the feeding ratio in Table 1, polytetramethylene glycol bis(p-aminobenzoate) and adipyl chloride were added to diphenylmethane diisocyanate at 60℃. After the addition was completed, the mixture was reacted at 85℃ for 3 hours, then cooled to 40℃ and mixed with WANNATE1631 and WANNATE 8617B. After stirring for 15 minutes, a sample was taken for analysis. The mass fraction of isocyanate group (NCO) was 24±0.5%. The mixture was then cooled and discharged.
[0062] Preparation of automotive glass edging products:
[0063] The reaction injection molding process was used. Materials A and B were mixed evenly according to the mass ratio in Table 1 using a high-pressure foaming machine, and then poured into a mold containing iron parts and surface-activated glass. After curing for 25 seconds, the mold was opened to obtain the automotive glass edging product. Alternatively, materials poured into a flat mold and cured for 25 seconds were opened to obtain the polyurethane test piece for automotive glass edging. The material temperature was maintained at 38℃, and the mold temperature was maintained at 120℃.
[0064] Example 2
[0065] Preparation of component A: The measured materials shown in Table 1 are added into the reactor and stirred at room temperature for 1 hour, and then discharged to obtain component A;
[0066] Preparation of Material B:
[0067] According to the feeding ratio in Table 1, dodecanediamine and adipic acid chloride were added to diphenylmethane diisocyanate at 60℃. After the addition was completed, the reaction was carried out at 75℃ for 1.5h, and then cooled to 40℃. The mixture was then mixed with WANNATE 1631 and WANNATE 8617B and stirred for 15min. After stirring, a sample was taken for analysis. The mass fraction of isocyanate group (NCO) was 26.3±0.5%. The mixture was then cooled and discharged.
[0068] Preparation of automotive glass edging products:
[0069] Using a reaction injection molding process, materials A and B are mixed evenly according to the mass ratio in Table 1 using a high-pressure foaming machine. The mixture is then poured into a mold containing iron parts and surface-activated glass. After curing for 30 seconds, the mold is opened to obtain the automotive glass edging product. Alternatively, the mixture is poured into a flat mold and cured for 25 seconds to obtain the polyurethane test piece for automotive glass edging. The material temperature is maintained at 36℃, and the mold temperature is maintained at 100℃.
[0070] Example 3
[0071] Preparation of component A: The measured materials shown in Table 1 are added to the reactor and stirred at room temperature for 1.5 hours, and then discharged to obtain component A;
[0072] Preparation of Material B:
[0073] According to the feeding ratio in Table 1, isophorone diamine and adipic acid chloride were added to diphenylmethane diisocyanate at 60℃. After the addition was completed, the mixture was reacted at 80℃ for 2 hours, then cooled to 40℃ and mixed with WANNATE 1631 and WANNATE 8617B. After stirring for 15 minutes, a sample was taken for analysis. The mass fraction of isocyanate group (NCO) was 24.6±0.5%. The mixture was then cooled and discharged.
[0074] Preparation of automotive glass edging products:
[0075] The reaction injection molding process is employed. Materials A and B are mixed uniformly according to the mass ratio in Table 1 using a high-pressure foaming machine. The mixture is then poured into a mold containing iron parts and surface-activated glass. After curing for 25 seconds, the mold is opened to obtain the automotive glass edging product. Alternatively, the mixture is poured into a flat mold and cured for 25 seconds to obtain the polyurethane test piece for automotive glass edging. The material temperature is maintained at 38℃, and the mold temperature is maintained at 110℃.
[0076] Example 4
[0077] Preparation of component A: The measured materials shown in Table 1 are added to the reactor and stirred at room temperature for 1.5 hours, and then discharged to obtain component A;
[0078] Preparation of Material B:
[0079] According to the feeding ratio in Table 1, dimethyldiaminodicyclohexylmethane and adipic acid chloride were added to diphenylmethane diisocyanate at 60℃. After the addition was completed, the mixture was reacted at 80℃ for 2 hours, then cooled to 40℃ and mixed with WANNATE 1631 and WANNATE 8617B. After stirring for 15 minutes, a sample was taken for analysis. The mass fraction of isocyanate group (NCO) was 27.1±0.5%. The mixture was then cooled and discharged.
[0080] Preparation of automotive glass edging products:
[0081] Using a reaction injection molding process, materials A and B are mixed evenly according to the mass ratio in Table 1 using a high-pressure foaming machine. The mixture is then poured into a mold containing iron parts and surface-activated glass. After curing for 25 seconds, the mold is opened to obtain the automotive glass edging product. Alternatively, the mixture is poured into a flat mold and cured for 25 seconds to obtain the polyurethane test piece for automotive glass edging. The material temperature is maintained at 35℃, and the mold temperature is maintained at 110℃.
[0082] Comparative Example 1
[0083] Preparation of component A: The measured materials shown in Table 1 are added into the reactor and stirred at room temperature for 2 hours, and then discharged to obtain component A;
[0084] Preparation of Material B:
[0085] The measured materials shown in Table 1 were added to the reactor and stirred at room temperature for 2 hours before being discharged to obtain component B, with a mass fraction of isocyanate group (NCO) of 25.1 ± 0.5%.
[0086] Preparation of automotive glass edging products:
[0087] The reaction injection molding process was used. Materials A and B were mixed uniformly according to the mass ratio in Table 1 using a high-pressure foaming machine, and then poured into a mold containing iron parts and surface-activated glass. After curing for 60 seconds, the mold was opened to obtain the automotive glass edging product. Alternatively, materials poured into a flat mold and cured for 60 seconds were opened to obtain the polyurethane test piece for automotive glass edging. The material temperature was maintained at 38℃, and the mold temperature was maintained at 120℃.
[0088] Comparative Example 2
[0089] Preparation of component A: The measured materials shown in Table 1 are added into the reactor and stirred at room temperature for 2 hours, and then discharged to obtain component A;
[0090] Preparation of Material B:
[0091] The measured materials shown in Table 1 were added to the reactor and stirred at room temperature for 2 hours before being discharged to obtain component B, with a mass fraction of isocyanate group (NCO) of 25.1 ± 0.5%.
[0092] Preparation of automotive glass edging products:
[0093] The reaction injection molding process was used. Materials A and B were mixed evenly according to the mass ratio in Table 1 using a high-pressure foaming machine, and then poured into a mold containing iron parts and surface-activated glass. After curing for 25 seconds, the mold was opened to obtain the automotive glass edging product. Alternatively, materials poured into a flat mold and cured for 25 seconds were opened to obtain the polyurethane test piece for automotive glass edging. The material temperature was maintained at 38℃, and the mold temperature was maintained at 120℃.
[0094] Comparative Example 3
[0095] Preparation of component A: The measured materials shown in Table 1 are added into the reactor and stirred at room temperature for 2 hours, and then discharged to obtain component A;
[0096] Preparation of Material B:
[0097] According to the feeding ratio in Table 1, polytetramethylene glycol bis(p-aminobenzoate) and adipic acid chloride were added to diphenylmethane diisocyanate at 60℃. After the addition was completed, the mixture was reacted at 85℃ for 3 hours, then cooled to 40℃ and mixed with WANNATE1631 and WANNATE 8617B. After stirring for 15 minutes, a sample was taken for analysis. The mass fraction of isocyanate group (NCO) was 24.1±0.5%. The mixture was then cooled and discharged.
[0098] Preparation of automotive glass edging products:
[0099] The reaction injection molding process was used. Materials A and B were mixed evenly according to the mass ratio in Table 1 using a high-pressure foaming machine, and then poured into a mold containing iron parts and surface-activated glass. After curing for 25 seconds, the mold was opened to obtain the automotive glass edging product. Alternatively, materials poured into a flat mold and cured for 25 seconds were opened to obtain the polyurethane test piece for automotive glass edging. The material temperature was maintained at 38℃, and the mold temperature was maintained at 120℃.
[0100] Comparative Example 4
[0101] Preparation of component A: The measured materials shown in Table 1 are added into the reactor and stirred at room temperature for 2 hours, and then discharged to obtain component A;
[0102] Preparation of Material B:
[0103] According to the feeding ratio in Table 1, polytetramethylene glycol bis(p-aminobenzoate) and adipyl chloride were added to diphenylmethane diisocyanate at 60℃. After the addition was completed, the mixture was reacted at 85℃ for 3 hours, then cooled to 40℃ and mixed with WANNATE1631 and WANNATE 8617B. After stirring for 15 minutes, a sample was taken for analysis. The mass fraction of isocyanate group (NCO) was 24±0.5%. The mixture was then cooled and discharged.
[0104] Preparation of automotive glass edging products:
[0105] The reaction injection molding process was used. Materials A and B were mixed evenly according to the mass ratio in Table 1 using a high-pressure foaming machine, and then poured into a mold containing iron parts and surface-activated glass. After curing for 25 seconds, the mold was opened to obtain the automotive glass edging product. Alternatively, materials poured into a flat mold and cured for 25 seconds were opened to obtain the polyurethane test piece for automotive glass edging. The material temperature was maintained at 38℃, and the mold temperature was maintained at 120℃.
[0106] Performance testing: The automotive glass edging products described in Examples 1-4 and Comparative Examples 1-4, including automotive glass edging articles and polyurethane test specimens, were subjected to the following tests:
[0107] 90° peel test
[0108] Hardness (Shore A) DIN 53505
[0109] Tensile strength and elongation at break DIN 53504
[0110] Tear strength ASTM D624
[0111] Linear thermal expansion coefficient ISO 11359-2:2021
[0112] The test results are summarized in Table 2.
[0113] Table 2 Test Results
[0114]
[0115] Comparative analysis of test results from the examples and comparative examples revealed that the high-performance automotive glass edging material of this invention exhibits excellent adhesion to glass and unheated iron parts under 25s rapid demolding conditions, and also demonstrates superior strength, toughness, and shrinkage properties. A comparison of Example 1 with Comparative Examples 1 and 2 shows that polyurethane materials without the diamine-modified isocyanate component described in this invention cannot simultaneously meet the requirements of rapid demolding and high performance. When the content of the diamine-modified isocyanate component is lower than the range described in this invention (Example 1 and Comparative Example 3), its peel strength is low, and its adhesion effect is poor. When the content of the diamine-modified isocyanate component is higher than the range described in this invention (Example 1 and Comparative Example 4), its tensile strength and other physical properties are poor.
[0116] In summary, the preparation method of this invention, through the synthesis of diamine-modified isocyanate and its combination with other modified isocyanates, and by adjusting the components of component A, produces a high-performance polyurethane material for automotive glass edging with a demolding time reduced to 25 seconds. Furthermore, the product exhibits excellent adhesion, strength, toughness, and shrinkage properties under 25-second demolding time and without heating of the iron component. This solves the problem that existing automotive sunroof glass edging materials cannot further improve production efficiency to ensure quality.
Claims
1. A polyurethane material for automotive glass edging, comprising the following components, in parts by weight: Material A includes: Polyether polyols with a functionality of 3: 60-90; Polyether polyols with a functionality of 2, 0~30; Alcohol chain extenders 2~16; Amine chain extenders: 0.1-4g; Catalyst 0.1~3; Anti-aging additives 0.8~8; Colorant 1~6; Material B comprises diamine-modified diphenylmethane diisocyanate and modified isocyanate; the diamine contains active hydrogen atoms; the preparation method of the diamine-modified diphenylmethane diisocyanate includes the following steps: The modified isocyanate is reacted with diphenylmethane diisocyanate and a diamine; the modified isocyanate is selected from one or more of carbodiimide-modified isocyanate, urethane-modified diisocyanate, and polyisocyanate.
2. The polyurethane material for automotive glass edging according to claim 1, characterized in that, Material A comprises: Polyether polyols with a functionality of 3: 75-80; 5-10 polyether polyols with a functionality of 2; Alcohol chain extenders 5-10; 1-2 amine chain extenders; Catalyst 0.1~0.5; Anti-aging additives 2-3; Colorant 3~4.
3. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The molar ratio of the active hydrogen atoms of the diamine to the isocyanate groups in the diphenylmethane diisocyanate is (0.001-0.2):
1.
4. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The diamine is C2-C 32 Diamine compounds.
5. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The diamine includes one or more of octanediamine, decanediamine, dodecanediamine, isophoronediamine, 4,4'-diaminodicyclohexylmethane, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, and polytetramethylene ether glycol-bis(p-aminobenzoic acid) ester.
6. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The modified isocyanate is selected from one or more of Wanhua Chemical's WANNATE1631, WANNATE8617B, and WANNATEPM200.
7. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The content of diamine-modified diphenylmethane diisocyanate in component B is 30-60%, based on the total weight of component B.
8. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The isocyanate group mass fraction of the B material is 16-30%.
9. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The isocyanate group mass fraction of the B material is 23-28%.
10. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The polyether polyol has a functionality of 3, a hydroxyl value of 10-80 mgKOH / g, and its polymerization units are propylene oxide and ethylene oxide, with the ethylene oxide accounting for 5%-50%.
11. The polyurethane material for automotive glass edging according to claim 1, characterized in that, The polyether polyol with a functionality of 2 has a hydroxyl value of 10-120 mgKOH / g, and the polymerization unit is propylene oxide, or propylene oxide and ethylene oxide, wherein the ethylene oxide accounts for 5%-50%.
12. A method for preparing the polyurethane material for automotive glass edging according to any one of claims 1-11, comprising the following steps: using a reaction injection molding process, mixing materials A and B at a mass ratio of A:B = 100:40-75 using a high-pressure foaming machine, then pouring the mixture into a mold containing an iron part and surface-activated glass, curing for 25-35 seconds, and then opening the mold to obtain the automotive glass edging product; wherein, The material temperature is maintained at 30-45℃, and the mold temperature is maintained at 80℃-120℃.
13. The method according to claim 12, characterized in that, A:B = 100:50-65 mass ratio.
Citation Information
Patent Citations
Preparation method of single-ingredient sag-resistant polyurethane waterproof paint
CN109321123A
Polyurethane elastomer for automobile glass encapsulation and preparation method thereof
CN101768251A
High-cohesiveness polyurethane material for automobile glass edge covering and preparation method thereof
CN111732703A